Aquinas on beauty - Sevier, Christopher Scott (Lexington Books, 2015)
This book comprehensively examines the aesthetic views of Thomas Aquinas, treating both the objective nature and the subjective human experience of beauty. It locates Aquinas's views in their historical context and illustrates their relations to other popular aesthetic views.